Sugar in the EEC (European News Agency BrusselsBE, 1987)
Compares increasing global sugar production to stagnant consumption. Suggests reasons for world market imbalances and notes the absence of an international agreement since 1984. Reviews prospects for the world sugar market. Examines EEC sugar regulations noting the controversy surrounding the common market organization and pointing out the need for new regulations. Discusses new problems caused by Spain and Portugal's entry into the EEC. Describes competition faced by sugar used in food from artificial sweeteners of industrial and plant origin and notes their impact on the European market. Discusses non-edible uses of sugar, the future of bio-ethanol and diversification efforts of sugar companies.
IDS